Shutting Down the Furnace: Preferential Killing of Cancer Cells with Mitochondrial-Targeting Molecules - M. Deus, Claudia; L. Santos, Gabriela; Loureiro, Rute; Vega-Naredo, Ignacio; Faneca, Henrique; J. Oliveira, Paulo (Current Medicinal Chemistry, 2015)
Mitochondria are organelles which play an important role not only in cellular metabolism but also in controlling pathways related with cell death, ionic and redox regulation. Alterations in mitochondrial metabolism are implicated in a variety of diseases, including cancer. Cellular and mitochondrial metabolism are both altered during the different stages of tumor development. As cancer cells have altered metabolic profiles, these alterations are a valid and promising target for anti-cancer agents. We hereby review several molecules that are in different stages of development and which target mitochondria in cancer cells. However, not all compounds are efficiently delivered into mitochondria, especially due to the difficulty of these agents to cross the membranes that surround the organelle, contributing to a loss of effectiveness and specificity. This led to the development of effective strategies aimed at delivering useful cargo to mitochondria, including the use of delocalized lipophilic cations coupled to useful molecules, or peptides that insert in mitochondrial membranes. Although several of those targeting strategies have still a very limited use against cancer cells, we present here the advantages and disadvantages of each combination.
Keywords: metabolic remodeling